Live fish highway: Uncovering the pathways that move millions of minnows across the United States - Victoria DeRooy; Amanda Hansen (PLoS ONE, 2026)
The spread of aquatic invasive species and pathogens over the last few decades has disrupted sportfishing, imposed economic costs on local industries, and threatened freshwater ecosystems. A significant but unquantified pathway for the spread of aquatic invasive species and pathogens in the United States is the long-distance transport of live baitfish. Despite the large scale of American baitfish production, policymakers lack high-quality, quantitative data on the movement of these fish across state lines, hindering rigorous risk assessment and regulatory efforts. This study addresses this knowledge gap by systematically collecting and synthesizing data on the interstate trade of live freshwater baitfish, obtained using freedom-of-information requests lodged with state governments across the United States. Our dataset captured the cross-border transport of 39.3 million live baitfish between 2022–24 in addition to 746 transport events where fish quantity was not recorded. Using this data, we detail trade flows disaggregated by species and explore the importance of key source states like Arkansas, South Dakota, and Minnesota. We highlight the variability in state government record-keeping, with data gaps existing in some states. By identifying high-traffic trade routes and quantifying species data, this study provides actionable insights for state agencies to strengthen biosecurity and environmental policy.